Au-Loaded Titanium Dioxide Nanoparticles Synthesized by Modified Sol-Gel/Impregnation Methods and Their Application to Dye-Sensitized Solar Cells. (7th April 2014) - Ninsonti, Hathaithip; Chomkitichai, Weerasak; Baba, Akira; Wetchakun, Natda; Kangwansupamonkon, Wiyong; Phanichphant, Sukon; Shinbo, Kazunari; Kato, Keizo; Kaneko, Futao
Abstract : Au-loaded TiO2 nanoparticles were synthesized by the modified sol-gel method together with the impregnation method. Anatase phase of TiO2 was obtained in all samples with an average particle size of 20 nm. For the enhancement of DSSCs, the dye-sensitized solar cells composed of the ITO/Au-loaded TiO2 /N-719/electrolyte/Pt were fabricated. Au-loaded TiO2 films were deposited by using squeegee method. Finally, the fabricated cells were studied upon an irradiation of solar light to study the performance. The fabricated cell with up to 1.0 mol% Au-loaded TiO2 could enhance the performance by localized surface plasmon effect and scattering property.